Isotherm and kinetic studies for the adsorption of methylene blue onto a novel Mn3O4-Bi2O3 composite and their antifungal performance - Al-Saeedi, Sameerah I.; Areej, Asfa; Qamar, Muhammad Tariq; Alhujaily, Ahmad; Iqbal, Shahid; Alotaibi, Mohammed T.; Aslam, Muhammad; Qayyum, Muhammad Abdul; Bahadur, Ali; Awwad, Nasser S.; Jazaa, Yosef; Elkaeed, Eslam B. (Frontiers in Environmental Science, 2023)
Metal oxide-based adsorbents are quite in for wastewater treatment because of their selectivity, stable structure and very low solubility in aqueous systems. To explore the adsorption of methylene blue (MB), Mn3O4-Bi2O3 adsorbents were made using a wet-impregnation technique with various concentrations of Mn3O4. The presence of Mn3O4 contents on the surface of monoclinic Bi2O3 was confirmed through representative scanning electron micrographs. The diffractions pertaining to cubic Mn3O4 and monoclinic Bi2O3 were noticed in the XRD pattern of 5% Mn3O4-Bi2O3 which confirm the composite nature of the adsorbent. XPS analysis revealed the existance of Bi 4f, Bi 4d, Bi 4p, Bi4s and Mn 2p core levels in Mn3O4-Bi2O3. The adsorption study divulged highest efficiency (~95% and qe = ~1.4 mgg-1) of 5% Mn3O4-Bi2O3 composite among other contestants in removing 30 ppm MB at 28 °C, pH 7 and 250 rpm. In addition to the determination of adsorption ability, the effect of preliminary dye concentration (5, 10, 20 and 30 ppm) and contact time (0.5-6 hrs) on the removal efficiency of prepared adsorbents were also monitored. The adsorption data from the batch experiments were evaluated using the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich-Kaganer (DRK) adsorption isotherms and pseudo 1st and 2nd-order kinetic models. The fitting of adsorption isotherms and kinetic models revealed the formation of adsorbate’s monolayer on the surface of adsorbents through the process of chemisorption. Through FTIR measurement, the MB adsorption onto the effective adsorbent (5% Mn3O4-Bi2O3) was also confirmed. Moreover, TGA analysis showed ~1.5% weight loss by 5% Mn3O4-Bi2O3 before MB adsorption whereas ~2.6% weight loss was noticed after dye adsorption onto the adsorbent. The antifungal activity was evaluated against the fungi A. solani and M. fructicola using the agar well diffusion technique. The 5% Mn3O4-Bi2O3 composites have exceptional antifungal characteristics compared to Bi2O3 and Mn3O4, with zone inhibition values of 58.6 and 53.9 mm, respectively.